Foodborne Titanium Dioxide Nanoparticles Induce Stronger Adverse Effects in Obese Mice than Non‐Obese Mice: Gut Microbiota Dysbiosis, Colonic Inflammation, and Proteome Alterations. Issue 36 (9th June 2020) - Cao, Xiaoqiong; Han, Yanhui; Gu, Min; Du, Hengjun; Song, Mingyue; Zhu, Xiaoai; Ma, Gaoxing; Pan, Che; Wang, Weicang; Zhao, Ermin; Goulette, Timothy; Yuan, Biao; et al.
Abstract: The recent ban of titanium dioxide (TiO2 ) as a food additive (E171) in France intensified the controversy on safety of foodborne‐TiO2 nanoparticles (NPs). This study determines the biological effects of TiO2 NPs and TiO2 (E171) in obese and non‐obese mice. Oral consumption (0.1 wt% in diet for 8 weeks) of TiO2 (E171, 112 nm) and TiO2 NPs (33 nm) does not cause severe toxicity in mice, but significantly alters composition of gut microbiota, for example, increased abundance of Firmicutes phylum and decreased abundance of Bacteroidetes phylum and Bifidobacterium and Lactobacillus genera, which are accompanied by decreased cecal levels of short‐chain fatty acids. Both TiO2 (E171) and TiO2 NPs increase abundance of pro‐inflammatory immune cells and cytokines in the colonic mucosa, indicating an inflammatory state. Importantly, TiO2 NPs cause stronger colonic inflammation than TiO2 (E171), and obese mice are more susceptible to the effects. A microbiota transplant study demonstrates that altered fecal microbiota by TiO2 NPs directly mediate inflammatory responses in the mouse colon. Furthermore, proteomic analysis shows that TiO2 NPs cause more alterations in multiple pathways in the liver and colon of obese mice than non‐obese mice. This study provides important information on the health effects of foodborne inorganic nanoparticles. Abstract : Oral consumption of food additive TiO2 (E171, 112 nm) or TiO2 NPs (33 nm) leads to a series of adverse effects in mice, such as gut microbiota dysbiosis, colonic inflammation, and altered hepatic and colonic proteome. Importantly, TiO2 NPs produce stronger adverse effects than TiO2 (E171), and obese mice are more susceptible to these effects.